Sex differences in flow cytometry–based platelet reactivity in stable outpatients suspected of myocardial ischemia. Issue 5 (15th May 2020) - Waissi, Farahnaz; Dekker, Mirthe; Bank, Ingrid E.M.; Korporaal, Suzanne J.A.; Urbanus, Rolf T.; de Borst, Gert J.; Pasterkamp, Gerard; Scholtens, Asbjorn M.; Grobbee, Diederick E.; Mosterd, Arend; de Kleijn, Dominique P.V.; Timmers, Leo
Abstract: Background: Antiplatelet therapy is the mainstay of secondary prevention of cardiovascular events. Studies suggest that women do not obtain equal therapeutic benefit from antiplatelet therapy compared with men. The link between sex differences in platelet biology and response to antiplatelet therapies is unclear. We therefore investigated the role of sex differences in platelet reactivity in a cohort of outpatients with chest pain, in response to treatment with antiplatelet agents. Methods: Platelet reactivity was measured in 382 randomly selected patients participating in the Myocardial Ischemia Detection by Circulating Biomarkers (MYOMARKER) study, an observational cohort study of outpatients suspected of myocardial ischemia. In all patients, blood was collected during diagnostic workup, and platelet reactivity was assessed with a flow cytometry–based platelet activation test that quantifies both platelet degranulation (P‐selectin expression) and platelet aggregation (fibrinogen binding to integrin αIIbβ3) in whole blood. Results: Platelet reactivity was higher in women compared with men when activated with protease activating receptor 1–activating peptide SFLLRN (PAR1‐AP) and adenosine 5′‐phosphate (ADP), independent of age, basal activation status, estimated glomerular filtration rate < 60, platelet count, statin use, the use of P2Y12 inhibitors, or the use of aspirin. P2Y12 inhibitor use strongly reduced fibrinogen binding after stimulation with PAR1‐AP, but only slightly reduced platelet P‐selectin expression. Calculation of the relative inhibition in P2Y12 users indicated 62% inhibition of the response toward ADP. Stratified analysis showed that women (n = 14) using P2Y12 inhibitors showed less inhibition of fibrinogen binding after PAR1‐AP stimulation than men (n = 38) using P2Y12 inhibitors. Conclusions: These findings call for further study of differential effects of P2Y12 inhibitors in women with suspected myocardial ischemia.